EFFECTIVENESS OF CHIROPRACTIC ADJUSTMENT IN LUMBAR PAIN IN CROSSFIT PRACTITIONERS - MOEHLECKE,DESIREE (2017)
ABSTRACT Objective: To evaluate the efficacy of acute chiropractic adjustment in individuals who practice CrossFit with regard to complaints of low back pain and the joint range of motion in this region. Methods: A randomized clinical trial comprised of CrossFit practitioners from a box in Novo Hamburgo-RS, of both sexes and aged 18 to 40 years who had low back pain at the time of the study. The following tools were used: Semi-structured Anamnesis Questionnaire, Visual Analog Scale, McGill Pain Questionnaire, and SF-36 Quality of Life Questionnaire. Individuals in the control group answered the questionnaires before and after CrossFit training. The chiropractic group performed the same procedure, plus pre-training chiropractic adjustment and joint range of motion (ROM) before and after lumbar adjustment. Results: There was a significant increase in pain in the control group, and a significant decrease in pain in the chiropractic group, including one day after the chiropractic adjustment. In the chiropractic group, the joint ranges of motion had a significant increase in flexion and extension of the lumbar spine after chiropractic adjustment. Conclusion: The chiropractic group achieved a significant improvement in pain level and joint range of motion, suggesting that acute chiropractic adjustment was effective in reducing low back pain.